Nutritional characterization of trees from the Amazonian piedmont, Putumayo department, Colombia - Riascos, A. R.; Reyes, J.; Aguirre, L. A. (Cuban Journal of Agricultural Science, 2020)
The nutritive characterization of trees from the Amazonian piedmont was carried out, in Putumayo department, Colombia. Random samples of six local forage species were collected: Tithonia diversifolia, Trichantera gigantea, Piptocoma discolor, Clitoria fairchildiana, Hibiscus rosa – sinensis and Solanum rugosum, with regrowth age of sixty days. The bromatological characterization was performed by NIRS spectroscopy and the content of anti-nutritional factors was qualitatively determined. For the statistical analysis, the statisticians, mean, standard deviation and coefficient of variation were taken into account. Piptocoma discolor highlighted for its high quality, since it showed the highest digestibility percentage (74.71) and higher protein values (21.52 %) and energy content (10.26 Mj/kg DM) with respect to the rest of the species. It was followed by Trichantera gigantea, with a digestibility percentage of 68.99; protein values of 20.34 % and energy content of 9.63 ME (Mj/kg DM). The Hibiscus rosa-sinensis species showed the lowest values of NDF (34.47 %) and ADF (17.13 %) and higher total starch content (3.31 %). In the mineral composition, the values of Zn and Cu for the tree Trichantera gigantea and the amount of Ca and P for Tithonia diversifolia were higher than the other forage plants. According to the characterization of the shrubs, it is concluded that the species Piptocoma discolor, Trichantera gigantea and Hibiscus rosa – sinensi have an adequate content of protein, energy and digestibility. The species Tithonia diversifolia, Clitoria fairchildiana, and Solanum rugosum have an appropriate mineral content and a moderate content of secondary metabolites. All have acceptable levels of nutritional components that make possible their use in animal feeding. Key words: silvopastoral, bromatological, Amazonia.